Transformation of household financial behavior under economic instability - Holovach, N. A.; Chervona, S. P. (Statistics of Ukraine, 2025)
The article addresses the urgent issue of the transformation of household financial behavior during a period of economic instability caused by a combination of war-related risks, inflationary pressures, and structural changes in the financial market. The purpose of the study is to provide a statistical analysis of the transformation of household financial behavior under economic instability, taking into account macroeconomic, wartime, and behavioral factors, as well as to identify the main trends and drivers shaping modern financial strategies of the population. The methodological framework includes time series analysis, index method, structural-dynamic analysis, shift coefficients, and the moving average method, which made it possible to combine quantitative assessment with behavioral interpretation. The study is based on official statistical data of the National Bank of Ukraine for 2020–2025, as well as indicative measures of consumer sentiment. The results reveal the patterns of transformation in household financial behavior. Credit and deposit activity is characterized by the dominance of short-term and highly liquid instruments, reflecting households’ desire to minimize risks. Consumer lending remains in a leading position, while mortgage lending is recovering gradually and predominantly in the national currency, indicating the strengthening role of the hryvnia and the reduction of the foreign currency component. Currency behavior experienced significant fluctuations: during the war period households increased demand for foreign currency as a safe-haven asset, but by 2025 signs of adaptation emerged, reflected in higher volumes of foreign currency sales. The dynamics of consumer confidence indices confirmed the contradictory nature of expectations: a rise in pessimism in the baseline dimension contrasted with partial optimism in the annual comparison, highlighting the decisive role of behavioral factors. The findings indicate that the transformation of household financial behavior is driven by a combination of macroeconomic, wartime, currency, and technological factors, and manifests itself in a shift from long-term to short-term strategies, the intensification of consumer lending, the strengthening of the national currency in the structure of financial obligations, and the expansion of cashless payments.